Implementasi Pembiasaan Berbahasa Inggris Anak Usia Dini - Lisnasari Benyamin, Rusyana; Hamid Patilima; Ajat (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
English language introduction from an early age is important because childhood is a English language introduction from an early age is important because childhood is a sensitive period in the development of language skills that can influence children's readiness to face future educational demands. This study aims to describe the implementation of English language habits in early childhood at TK A Tiara School, East Jakarta. The study used a qualitative approach with a case study type. Data were collected through participatory observation of learning activities, in-depth interviews with teachers and the principal, and documentation studies of lesson plans and child development records. Data analysis was carried out through data reduction, data presentation, and conclusion drawing stages to obtain a comprehensive picture of the process of English language habits. The results showed that consistent English language habits have a positive impact on early childhood language skills. Improvements were seen in the ability to understand simple instructions, vocabulary mastery, and children's courage in using English. Observational data showed that the number of children able to understand simple instructions increased from 6 to 13 children out of a total of 15 children. Vocabulary mastery increased from an average of 10–15 words to 30–40 words. In addition, children's courage in answering questions increased from 5 to 13 children, while spontaneous use of English increased from 3 to 12 children.